Numerical modelling of Tb3+ doped selenide-chalcogenide multimode fibre based spontaneous emission sources - Sujecki, S.; Sójka, L.; Bereś-Pawlik, E.; Sakr, H.; Tang, Z.; Barney, Emma R.; Furniss, David; Benson, Trevor M.; Seddon, Angela B. (Springer, 2017)
A model is developed of a terbium (III) ion doped selenide chalcogenide glass fibre source that provides spontaneous emission within the mid-infrared (MIR) wavelength range. Three numerical algorithms are used to calculate the solution and compare their properties.